Produção e caracterização de filmes biodegradáveis de proteína isolada de soja para o encapsulamento de Bacillus megaterium - Godoy, Camila Reis de (Universidade Federal de São Carlos, 2024)
The use of plant growth-promoting microorganisms has been widely cited as a sustainable and promising alternative to chemical fertilizers. Microorganism encapsulation offers notable advantages, as the cells are protected against stresses and a conducive environment for increased viability is established, leading to enhanced performance in both plants and soil. Isolated Soy Protein (ISP) is a low-cost, biodegradable product available globally. Thus, microbial inoculant formulations utilizing Isolated Soy Protein as a matrix hold significant commercial potential. This project aims to develop and characterize biodegradable films using Isolated Soy Protein as a matrix for encapsulating the bacterium B. megaterium B119, to create a platform for controlled release of biofertilizers. Additionally, it evaluates cell viability, storage time, and changes in physicochemical characteristics induced by different pH levels. The approach is based on the need for sustainable alternatives to conventional fertilizers, aiming to mitigate environmental impacts. Films were produced using the casting technique and characterized by FTIR, SEM, contact angle, permeability, swelling, and solubility. The objective was to assess encapsulation efficacy, release profile, and post-storage viability. Results showed that the pH 7.0 film had a darker coloration and higher swelling rate, favoring its release. However, in accelerated viability analysis, the best values were observed for the pH 5.0 film. In summary, the results indicate that pH significantly influences various properties of films made with Isolated Soy Protein (ISP), with the pH 5.0 film standing out for its controlled release capability and viability, and the pH 6.0 and 7.0 films for their resistance to adverse environmental conditions such as UV radiation. These findings suggest promising potential for application in the fields of biofertilizers and controlled release of microorganisms.
Production and characterization of biodegradable films using isolated soy protein for the encapsulation of Bacillus megaterium
Keywords: Biofertilizantes; Soja; Microrganismos; Encapsulamento; Biofertilizers; Soy; Microorganisms; Encapsulation; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE::MICROBIOLOGIA AGRICOLA; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA